Thalassemia, biobanking infrastructures, and personalized stem cell therapies in Chennai - Panwar, Amishi (Frontiers in Sociology, 2023)
Thalassemia and Leukemia and related blood disorders are approved for blood stem cell transplant in India. For a stem cell transplant to be successful, the Human Leukocyte Antigen (HLA) complex located on the arm of chromosome six must be a match between the cord blood donor and the recipient. In the quest to find an exact blood stem cell match for an individual, the HLA becomes the node at the center of community genetics where the HLA match is sought (not necessarily successful) in the extended family, the same caste, language, and ethnic (both national and the diaspora) groups. By considering Thalassemia as a case study, how do we understand personalized stem cell therapies within bio banking infrastructures in Chennai? How do social categories get entwined with biological materials like cord blood?